Systematic Spectral Lag Analysis of Swift Known-z GRBs - Yuta Kawakubo; Takanori Sakamoto; Atsumasa Yoshida; Demos Kazanas (Advances in Astronomy)
The difference of photon arrival time, which is known as spectral lag, is well known characteristics of gamma-ray bursts (GRBs). In particular, long duration GRBs show a soft lag which means that high energy photons arrive earlier than soft photons. The lag-luminosity relation is the empirical relationship between the isotropic peak luminosity and the spectral lag. We calculated the spectral lags for 40 known redshift GRBs observed by Swift addition to the previous 31 GRB samples. We confirmed that most of our samples follow the lag-luminosity relation. However, we noticed that there are some GRBs which show a significant scatter from the relation. We also confirm that the relationship between the break time and the luminosity of the X-ray afterglow (so-called Dainotti relation) extends up to the lag-luminosity relation.